Vitamin E plays a protective role while acrylamide administration disrupted the placenta structure in pregnancy: An experimental study - Erdemli, Zeynep; Erman Erdemli, Mehmet (Annals of Medical Research, 2021)
Aim: The present study aimed to investigate possible variations in the placental tissues of rats upon acrylamide (AA) and vitamin E (Vit E) applications between the 0th and 20th days of pregnancy. Materials and Methods: Pregnant rats were divided into control, corn oil, AA, Vit E, AA + Vit E groups. At the end of the experimental period, the abdominal tissue of pregnant rats that were anesthetized with xylazine-ketamine was incised, and the placental tissues that connect the mother and the fetus were removed. Biochemical analyses were conducted based on the malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), protein, total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI) levels in placental tissues.Results: It was observed that there were no differences between the control and corn oil groups. It was determined that AA administration increased MDA, TOS and OSI levels and decreased SOD, CAT, TAS, and GSH levels when compared to all other groups. Vit E administration increased GSH, TAS, SOD and CAT levels when compared to all other groups. In the AA + Vit E group, it was observed oxidative stress parameters approached control group levels.Conclusion: Administration of 10 mg/kg/bw AA led to placental oxidative stress in pregnant rats. This action induced by AA was not only through the increase in MDA, TOS and OSI levels, but also through the reduction of GSH, SOD, CAT, and TAS levels, leading to the deterioration of the oxidant-antioxidant balance. Administration of 100 mg/kg/bw Vit E increased antioxidant capacity in placental tissue. To minimize AA-induced toxicity exposure, we recommend the consumption of sufficient Vit E throughout life not only during pregnancy.
Keywords: Placenta; acrylamide; vitamin E; pregnancy; oxidative stress; rat